2018
DOI: 10.3390/ijerph15020224
|View full text |Cite
|
Sign up to set email alerts
|

Are Perceived and Objective Distances to Fresh Food and Physical Activity Resources Associated with Cardiometabolic Risk?

Abstract: Perceived and objective measures of neighbourhood features have shown limited correspondence. Few studies have examined whether discordance between objective measures and individual perceptions of neighbourhood environments relates to individual health. Individuals with mismatched perceptions may benefit from initiatives to improve understandings of resource availability. This study utilised data from n = 1491 adult participants in a biomedical cohort to evaluate cross-sectional associations between measures o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(52 citation statements)
references
References 69 publications
0
52
0
Order By: Relevance
“…Methods used in this group of studies were heterogeneous, with no two studies measuring the same food retail environment characteristic. Five studies found no significant association(s) . Two studies found significant associations in the hypothesized direction, whereby healthier food retail environments were associated with lower measures of people with obesity) .…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…Methods used in this group of studies were heterogeneous, with no two studies measuring the same food retail environment characteristic. Five studies found no significant association(s) . Two studies found significant associations in the hypothesized direction, whereby healthier food retail environments were associated with lower measures of people with obesity) .…”
Section: Resultsmentioning
confidence: 89%
“…The same study reported a significant positive correlation between healthiness of the food retail environment, measured using the Relative Food Environment Index, and four diet scores (total diet, fruit and vegetable, sugary drink and discretionary food—higher being healthier for all scores) . Five studies reported non‐significant associations between fruit and vegetable intake and proximity to and/or density of supermarkets and/or greengrocers/fruit and vegetable retailers, chain supermarkets and fast food outlets or the introduction of a new fast food outlet on fast food consumption …”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…These shortcomings of the place-based perspective of accessibility paved the way for the emergence of person-based accessibility measures, which assess accessibility on an individual level. An increasing number of studies investigate the perceived distances vs. real or Euclidean distances [58,[62][63][64], usually, at an aggregated level to reflect locational privacy. These studies may use concepts of both place-based and people-based approaches-if it is possible to distinguish such approaches.…”
Section: Accessibility Studiesmentioning
confidence: 99%